Design of a Spring-Finger Potato Picker and an Experimental Study of Its Picking Performance - Lihe Wang; Fei Liu; Qiang Wang; Jiaqi Zhou; Xiaoyu Fan; Junru Li; Xuan Zhao; Shengshi Xie (Agriculture, 2023)
To address the problems of low pickup rates and high rates of wounds in the mechanised harvesting of potatoes under sectional harvesting conditions, a spring-finger potato picker was designed and its overall structure and working principles were described. The kinematic principle of the spring-finger was analysed based on the picking constraints, and the kinematic parameters of the picker were determined. A response surface Box–Behnken Design test design was used to carry out a quadratic orthogonal rotational test, with the speed of the spring-finger, the forward speed of the machine, and the embedded depth as test factors, and the loss rate and the wounded potato rate as evaluation indicators. The test results were optimised and analysed. When the spring-finger speed was 19.57 r/min, the forward speed was 0.61 m/s and the embedded depth was 71.31 mm, the loss rate was 1.18%, and the wounded potato rate was 5.71%. The optimised data were verified, and the results showed that the loss rate of the spring-finger potato picker was 1.48% and the wounded potato rate was 4.98%, meeting the potato picking and harvesting requirements. The research can provide a theoretical basis and design reference for the development and application of sectional potato harvesting machinery.